Political Acceptability of Private Financing in Hungary - Laszlone Tanczos; Ágnes Kosztyó; Meszaros Ferenc (European Regional Science Association (ERSA), 2005)
This study is based on the research of TIPP - Transport Institutions in the Policy Process - project in the EC's 5th Framework Programme. It is generally acknowledged that the implementation of regulations faces many problems of the existing institutional system. Beside all its affection may thicken on with passing of social, economics and structural changes in the same time. In the course of the transition period nascent and existing circumstances can propose several questions about its equitableness, acceptability and conduciveness and it can be a lesson for the future organising. Hungary is also undergone substantial changes during last decade. This transition created new responsibilities in road management (e.g. creating the possibility of private financing) and strengthened the accounting discipline and transparency, but the implementation of regulations still faces to many problems of the existing institutional system. The missing financial sources for development and the lasting financial funding of maintenance in the road sector lead to a substantially fall in the asset value of the national road network. On the public side - ministry, State motorway company - the continuous structural and regulatory changes resulted in an uncertainty even at the decision making level within the institutions. In Hungary the decision makers like to enhance the State revenue generating financial resources for operation, maintenance and for development as well in future plan. A well-financed and extended motorway network could improve social cohesion and the economic growth, which is still missing in such countries as Hungary. In the Hungarian practice there is a clear tendency that is in cost allocation between road users with commonly accepted pricing principles but time is needed for implementation. This study contributes to achieve these goals discussing the differing common European and Hungarian objectives, and find acceptable criteria to be taken into account in setting up of transport policies in the Hungarian practice.
Keywords: 330